Parents' perspectives on counseling for fetal heart disease: what matters most? - Kovacevic, Alexander; Wacker-Gußmann, Annette; Bär, Stefan; Elsässer, Michael; Mohammadi Motlagh, Aida; Ostermayer, Eva; Oberhoffer-Fritz, Renate; Ewert, Peter; Gorenflo, Matthias; Starystach, Sebastian (Journal of Clinical Medicine, 2022)
After diagnosis of congenital heart disease (CHD) in the fetus, effective counseling is considered mandatory. We sought to investigate which factors, including parental social variables, significantly affect counseling outcome. A total of n = 226 parents were recruited prospectively from four national tertiary medical care centers. A validated questionnaire was used to measure counseling success and the effects of modifiers. Multiple linear regression was used to assess the data. Parental perception of interpersonal support by the physician (β = 0.616 ***, p = 0.000), counseling in easy-to-understand terms (β = 0.249 ***, p = 0.000), and a short period of time between suspicion of fetal CHD, seeing a specialist and subsequent counseling (β = 0.135 **, p = 0.006) significantly improve “overall counseling success”. Additional modifiers (e.g., parental native language and age) influence certain subdimensions of counseling such as “trust in medical staff” (language effect: β = 0.131 *, p = 0.011) or “perceived situational control” (age effect: β = 0.166 *, p = 0.010). This study identifies independent factors that significantly affect counseling outcome overall and its subdimensions. In combination with existing recommendations our findings may contribute to more effective parental counseling. We further conclude that implementing communication skills training for specialists should be considered essential.
Gesehen am 10.01.2022